Design of A Web-Based Community Administration Application Using the Agile Scrum Method in the Tanjung Lengkong RT Environment - Pahlevi, Dyo Rizqal; Junaedi, Ifan; Sianipar, Anton Zulkarnain (Universitas Mohammad Husni Thamrin, 2025)
The rapid development of information technology has brought significant changes to various aspects of life, including the community management system at the most basic level, namely the Neighborhood Association (RT). Ideally, this technological advancement can be utilized to improve service efficiency, data transparency, and more effective communication between RT administrators and their residents. However, in reality, many RTs still implement traditional administrative systems, such as manual recording, information delivery through physical flyers, and non-computerized mail services. This is something the author observed directly in the Tanjung Lengkong RT environment, where the still-manual administrative process often causes several obstacles. If conditions like this continue, it is feared that it will give rise to more complex social problems in the future, such as a lack of public trust in RT administrators, minimal participation in environmental programs, and the potential for delays in the distribution of aid or important information from the government. This study discusses the design of a web-based community administration application using the Agile Scrum method. The development focus is directed at the need for an efficient and structured RT management system. This study uses a qualitative descriptive approach to describe the system implementation process and user responses to the developed system. The final result is a prototype of an RT administration application that can be used to support the digitalization process of public services.